Beth Harmon’s Literacy As Power and Its Impact On Gender Roles In Walter Tevis’ The Queen’s Gambit - Novi Anti (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2023)
Literacy practices are often represented in various media through literary works such as novels, films, and others. Literary works are the result of literacy practices, and the values of literacy practices are sometimes incorporated into literary works through the characters in them. However, readers often ignore the value of literacy in literary works. Literacy is more than just the cognitive ability to read and write; it also refers to what people do with literacy. Literacy can be represented in several forms and used for different purposes, one of which is power. The literacies in The Queen's Gambit novel represent power in the eyes of Beth Harmon. The power of literacy gained by Beth is represented by improving social class and increasing popularity, which later impacted her gender roles. The purpose of this study is to display literacy representation as power and its impact on gender roles in Beth Harmon, the main character in The Queen's Gambit novel. The method used is textual analysis, the main source of which is the novel The Queen's Gambit by Walter Tevis, using the framework of New Literacy Studies (NLS) as a social practice of literacy perspective using the theory of Williams and Zenger (2007) from their book